2010
DOI: 10.1071/ah09777
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the rebound: improving care transition in hospital discharge processes

Abstract: Background. Unplanned readmissions of recently discharged patients impose a significant burden on hospitals with limited bed capacity. Deficiencies in discharge processes contribute to such readmissions, which have prompted experimentation with multiple types of peridischarge interventions.Objective. To determine the relative efficacy of peridischarge interventions categorised into two groups: (1) single component interventions (sole or predominant) implemented either before or after discharge; and (2) integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 55 publications
2
53
1
2
Order By: Relevance
“…The results are consistent with an Australian meta-review of controlled trials that concluded that telephonic follow up was an effective strategy for specific high-risk populations, such as older patients and those with heart failure, 36 but also indicate that a scalable program can be effective in more than just these specific high-risk populations. The results of the present study are also consistent with results from a previous study of telephonic-only post-discharge support delivered by Healthways that exhibited a significant effect on hospital readmissions.…”
Section: Discussionsupporting
confidence: 77%
“…The results are consistent with an Australian meta-review of controlled trials that concluded that telephonic follow up was an effective strategy for specific high-risk populations, such as older patients and those with heart failure, 36 but also indicate that a scalable program can be effective in more than just these specific high-risk populations. The results of the present study are also consistent with results from a previous study of telephonic-only post-discharge support delivered by Healthways that exhibited a significant effect on hospital readmissions.…”
Section: Discussionsupporting
confidence: 77%
“…50 Early assessment of caregiver availability and inclusion in education may increase caregiver support of the self-care plan. Although caregiver roles were valued in some multicomponent transition of care programs that focused on high-risk patients, 51 demands placed on caregivers to monitor complex self-care and medical regimens and to deal with emotional distress, disturbed sleep, and patient rehospitalization 40,41 can be daunting. Caregiver roles and outcomes during transitions of care are not well described and require more clarification.…”
Section: Caregiversmentioning
confidence: 99%
“…[1], [2] This study aims to describe the predictors of mortality amongst geriatric patients admitted under General Medicine in a regional Australian hospital.…”
Section: Mortality Predictors In Hospitalised Geriatric General Medicmentioning
confidence: 99%